ANALISIS PROGRAM BONGKAR RATOON TANAMAN TEBU UNTUK AKSELERASI PENINGKATAN PRODUKTIVITAS GULA (STUDI KASUS DI WILAYAH PABRIK GULA SEMBORO KABUPATEN JEMBER PROVINSI JAWA TIMUR) - Badiatud Durroh (AGROISTA : Jurnal Agroteknologi, 2018)
The purpose of this research is to know the difference of sugarcane productivity, yield and crystal productivity between sugar cane plant and ratoon unloading system and ratooncane system. The research was conducted on July 17, 2017 to July 31, 2017 at PT. Perkebunan Nusantara XI Semboro Sugar Factory in Rejoagung Semboro, Jember East Java. The research method used in this research is descriptive analysis method. Data types use primary data and secondary data. Variable in this research consist of two independent variable that is sugar cane discharge system of ratoon and sugarcane crop of ratoon cane system. The parameters observed were: p roductivity of sugarcane (ton / ha) during last 4 years (2013 - 2016), Rendement (%) during last 4 years (2013-2016), crystal productivity (ton / ha) during last 4 years (2013 -2016). The data were analyzed by using T test two independent variables were T independent sample test. The results showed that the productivity of sugarcane with ratoon unloading system is higher compared with keprasan system. Or in other words, unloading ratoon can increase the productivity of sugar cane significantly. The yield of sugar cane with ratoon unloading system is higher compared with ratoon cane system. Or in other words, unloading ratoon can increase the rendement of sugar cane significantly. The productivity of sugar cane with ratoon unloading system is higher than the keprasan system. Or in other words, unloading ratoon can increase the productivity of sugar cane significantly. Keywords : sugarcane, productivity, yield, crystal, unloading ratoon, ratoon cane